Quality Cost Analysis of Selected Construction Works (Proceedings of Faculty of Civil Engineering, 2019)
The paper deals with the issue of the quality cost of construction works. This problem, especially in our country, has not significantly been explored. At present, quality plays an important role in all activities, including construction. It is well known that meeting the required quality is also one of the essential benchmarks of a successful realization of construction projects. Of course, achieving quality requires spending financial resources. However, it is common that these costs are included in total costs. Thus, not enough attention is paid to their quantification. It is expected that the problem of quantification of these costs will gain more importance with further growth of construction project complexity and quality requirements. As a contribution to solving this problem, a research was conducted through a survey among the employees of construction companies by collecting data on quality costs. The research attempted to determine whether the quality cost depend on time and costs of labor and materials of construction work operation. Criteria for the selection of construction works were the frequency of appearances in building projects and the number of work operations they consisted of. Five works were selected (making formwork for foundation, reinforcing with steel rods, concreting C16/20, wall masonry, plastering of walls), each consisting of at least three work operations. Percentage shares of quality costs are determined in selected works and then compared with shares of time and costs of labor and materials. Time and cost percentage shares were calculated using the norms of construction works while the shares of the quality cost were estimated based on the data obtained by the survey. The results have shown that the amount of quality cost in construction work is not necessarily proportional to the time and cost of the work operation. In other words, the measure of the achieved quality is not merely the time of work invested in its achievement, as well as quality of embedded materials, but the quality of the work of the contractor. Additionally, when a work operation is approached with necessary care, the possibility of error, additional work, and therefore additional quality costs are also reduced.
Keywords: quality; construction work; work operation; time; cost; quality cost